Upcycling of postconsumer recyclate polypropylene into low warping and high toughness 3D printable filaments - Gopal, Animesh; Patil, Prashant; Pol, Harshawardhan; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2025)
Polypropylene (PP) is widely used in commodity applications owing to its chemical stability, mechanical properties and low cost. However, almost 50% of the produced PP ends up as postconsumer waste (PCW) within a short period of usage. Being a non-biodegradable polymer, recycling PCW PP is important to mitigate plastic waste in landfills. Nonetheless, recycling or upcycling postconsumer recyclate (PCR) PP into valuable resources without deterioration in physical and mechanical properties is a challenge. This report presents an approach to upcycle PCR polypropylene (rPP) into high quality 3D printing filament that not only prints with very low warpage but with significantly high elongation at break and toughness. Incorporation of poly(butylene adipate-co-terephthalate) (PBAT) along with maleic anhydride grafted polypropylene (MAPP) in specific proportions led to a significant enhancement in mechanical properties, miscibility, crystallization behavior, and 3D printability. rPP/PBAT blends with 20 wt % PBAT and 10 wt % MAPP exhibited a 62-fold enhancement in elongation at break over rPP (from 1.88 to 118.29%) and a 72-fold increase in toughness (from 2 to 143.60 kJ/m3) with almost similar tensile strength. The final printed components had better layer adhesion and structural stability with a dramatic decrease in warpage, from 25.82% for pristine rPP to only 7.86% for rPP/PBAT blend. Isothermal crystallization studies and data analysis using the Avrami equation showed that crystallization half-time (t 1/2), which measures the duration needed for half of the total crystallinity to form, increased from 12.6 s for rPP to 66 s for the rPP/PBAT blend. This report demonstrates an approach to upcycle PCR PP, a positive step toward realizing the goals of circular economy and sustainable additive manufacturing.
Keywords: Crystallization; FFF 3D printing; polypropylene/poly(butylene adipate-co-terephthalate)blends; toughness; warpage